MUTU PELAYANAN DAN TARIF PELAYANAN TERHADAP MINAT PEMANFAATAN ULANG JASA RAWAT INAP DI RUMAH SAKIT MARDI MULYA TRENGGALEK - Mira Eni Prasetya; Byba Melda Suhita (STRADA : Jurnal Ilmiah Kesehatan, 2017)
Interests to revisit on inpatient services should be considered by the health services to create patient loyalty. For that must be known several factors that affect the interest of such perceptions of the quality or suitability of the cost. The purpose of this study was to determine the effect of service quality and cost of service to the interests are visits inpatient services at the hospital. Design of this research is an analytic correlation with cross sectional approach with a total population of 68 respondents with a sampling technique that Stratified Random Sampling and obtained a sample of 58 respondents. Data obtained from the questionnaire to determine the effect of independent were variables service quality and cost of service with the dependent variable was interest to revisit by using ordinal regression test. The results showed that out of 58 respondents mostly interested in re-hospitalization visits as many as 35 respondents (60.3%). Based on the statistical test Ordinal Regression showed there is effect of service quality and cost of service to the interests of revisits inpatient services with siginifikansi value = 0.000 <α 0.05, then reject H0. While individual test only quality of service affect the interest revisit with p value 0,002 <α 0.05. Time by the time people do not make the cost or the price as the only consideration in the reuse of products or services, but they also consider other factors such as value, service, product or quality.